Genetic Validation of Advanced Backcross-derived Rice Lines for Nilaparvata lugens (Stal) Resistance via SSR Markers - Kumari, R. Prathima; Anusha, Ch.; Kumar, R. Shravan; Hari, Y.; Prasad, K. Rajendra; Gowda, M. A. Prajwal; Akhilandeshwari, D. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Nilaparvata lugens (Stål), referred to as the brown planthopper (BPH), is a serious threat to paddy cultivation. It inflicts damage by feeding on rice plants and serves as a vector for the rice ragged stunt virus and the rice grassy stunt virus, both of which contribute to significant yield losses. The research was conducted during kharif-2021 at Regional Agricultural Research Station (RARS), Warangal. SSR markers RM 3766 (for the Bph3 gene) and RM 586 (for the Bph4 gene) were used for molecular confirmation of resistance in BPH. The study revealed the presence of resistance genes in all resistant and moderately resistant lines, except Siddhi-BC2F6 BPH-BL-24, which was heterozygous (partial resistance) for Bph3, and Siddhi-BC2F6 BPH-BL-11 and Siddhi-BC2F6 BPH-BL-52, which were heterozygous (partial resistance) for Bph4. This genetic validation using SSR markers not only confirms the successful introgression of resistance traits but also enhances the efficiency of breeding programs aimed at developing durable BPH-resistant rice cultivars.